Empowerment of Village Communities Around Forest Through Joint Community Forest Management (PHBM) in Kedungsuren Village - Saerozi Saerozi; Dian Adi Perdana; Najahan Musyafak; Dedy Susanto; Lukmanul Hakim; Koree Jarong (Prosperity)
Community empowerment through the Joint Community Forest Management (PHBM) Program has been implemented so far by the Kendal Forest Management Unit (KPH) together with the community and has succeeded in improving the community economy in Kedungsuren Village. The aim of this study; is (1) knowing the causes of community poverty in Kedungsuren Village, (2) knowing community empowerment through Community Forest Management (PHBM). In this type of qualitative research, with a descriptive approach and case studies, the research locus in Kedungsuren Village is in the KPH Kendal forest area. Data collection using interviews, observation, and documentation. The research analysis uses qualitative description. The results of this research show that (1) the causes of poverty are poor quality of human resources, lack of agricultural land, lack of capital, agricultural products sold to intermediaries, lack of skills in managing livestock, and lots of agricultural pests. (2) Community empowerment through Joint Community Forest Management (PHBM), namely through community skills and additional business capital, entrepreneurial training for LMDH members, socialization and counseling for LMDH, community involvement in PHBM programs starting from planning to the monitoring stage and evaluation, and use of shared funds by LMDH.